2017
DOI: 10.18632/oncotarget.15058
|View full text |Cite
|
Sign up to set email alerts
|

mTOR/autophagy pathway in the hippocampus of rats suffering intermittent hypoxia preconditioning and global cerebral ischemia-reperfusion

Abstract: We explored the role of mTOR/autophagy pathway in the aggravation of cerebral ischemia-reperfusion nerve injury caused by intermittent hypoxia. Eighty male wistar rats were divided into four groups by the random number method: sham operation group (SO group, n=20), cerebral ischemia-reperfusion group (I/R group, n=20), intermittent hypoxia and cerebral ischemia-reperfusion group (IH+I/R group, n=20), intermittent hypoxia and cerebral ischemia-reperfusion group plus mTOR inhibitor group (inhibitor group, n=20).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Moderate autophagy induced by mild hypoxia can enhance the ability of nerve cells to resist changes in the external environment, thus improving the survival rate of cells [5]. However, excessive activation of autophagy caused by severe hypoxia can lead to injury and apoptosis of nerve cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moderate autophagy induced by mild hypoxia can enhance the ability of nerve cells to resist changes in the external environment, thus improving the survival rate of cells [5]. However, excessive activation of autophagy caused by severe hypoxia can lead to injury and apoptosis of nerve cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies had mainly focused on the study of brain cell apoptosis, while the effects of HIF-1a on autophagy remain unexplored. Indeed, recent studies have revealed the importance of cell autophagy in the protection of the brain cells [ 3 , 15 21 ]. However, a role of HIF-1a in the regulation of brain cell autophagy after IR has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral ischemia reperfusion (IR) causes cerebral injury and brain dysfunction due to oxidative damage and apoptotic cell death [ 2 , 3 ]. Although it is critical to provide reperfusion to the ischemic tissue at earliest stage, the outcome may not be ideal due to the presence of free oxygen radicals in IR [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation